THE EFFECT OF GELLING AGENT ON THE MICROPROPAGATION OF COMMON LILAC (SYRINGA VULGARIS L.) - Orsolya Borsai; Doina Clapa; Alexandru Fira; Monica Hârța; Adelina Dumitraș; Rodica Pop; Doru Pamfil (Agricultura, 2017)
In order to assess the effect of gelling agents upon lilac in vitro proliferation rate, eight types of gelling agents were tested, at concentrations considered to be optimal, based on preliminary tests as follow: 3 g/L Fibrous Agar, 6g/L Daishin Agar, 4 g/L Gelcarin, 2 g/L Gelrite, 15 g/L Isubgol, 4 g/L Micro Agar, 6 g/L Phyto Agar and 4 g/L Plant Agar. The culture media was Murashige & Skoog (MS) supplemented with 4 mg/L 6-benzylaminopurine (BAP). The plant material consisted of shoots picked from in vitro cultures on MS+0.5 mg/L BAP gelled with Plant Agar. The highest multiplication rate was 3.76, obtained in the experimental treatment with the media gelled with 15 g/L Isubgol, while the lowest proliferation rate was 1.4, on the media gelled with Daishin Agar. The shoots obtained in these eight experimental treatments were rooted ex vitro and acclimatized using the floating perlite method, in two experimental treatments: one with hormone-free floating perlite and one supplemented with 1mg/L indole-3-butyric acid (IBA). The highest rooting and acclimatization percentage (90%) was obtained in the hormone-free floating perlite experimental treatment, from shoots obtained in the media gelled with 6 g/L Daishin Agar.